An hypothetical reconstruction of Galileo Galilei’s wine cellar at Villa il Gioiello - Fiorino, Davide; Vergari, Daniele; Viviani, Carlo (Il Colle di Galileo, 2019)
The Accademia dei Georgofili has been involved in the museum enhancement of Galileo’s last home, to define a reconstructive hypothesis of the wine cellar and kitchen in the scientist’s villa. Starting from the documentation published on Galileo’s correspondence and thanks to a historical-documentary research on the viticulture and kitchens of the time, a reconstruction of the rooms has been proposed.